An Overview of Thermal and Non-Thermal Food Processing and Preservation Methods (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
Thermal food processing technology had been in existence since the creation of human but recently industries are beginning to adopt the use of non-thermal food processing technology due to the challenges associated with the former like high energy consumption, degradation of food nutritive contents and high operational cost. Basically, food processing techniques are used to pasteurize, preserve taste, retain or improve nutrient contents and increase shelf life of food on storage. However, there is an increased awareness for the consumption safe and high nutritional food which has led to consumers’ demand for processed food to retain natural flavour, pigment, safe, high nutritive value with an extended shelf life long enough for sales and home storage before consumption.  These demands led to the continuous advancement in food processing industry to design techniques capable of retaining nutritive quality and organoleptic properties of food requiring little or no heat energy to process. In addition to the known novel processing methods like freeging, freeze-drying, ohmic heating and microwave, there is an increasing interest in developing other novel methods to achieve better food sterilization and preservation which includes high hydrostatic pressure process (HHP), pulsed electric field (PEF), cold plasma technology (CP). However, the later can lead to oxidation of lipids and loss of colour and flavour based on time of exposure. Therefore, this short review presents an overview of thermal and non-thermal food processing technologies with the underlining principles, uses and limitations of few of them.
Keywords: Food processing; Thermal; Non-thermal; Pasteurization; Shelf life